Peaceful Coexistence Through the Concepts of Brahmavihārās of Buddhism and Maqāṣid al-Sharīʿa of Islam: A Content Analysis - Mohamed Ashath (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
To understand every religion, it is vital to study the main sources, the specific religious scriptures of a particular religion. In order to draw a conclusion about the core message of religion, it is not scientific to observe only the practices of the adherents of a certain religion. Although Buddhism and Islam have been considered as religions of peace, the meeting of Buddhists and Muslims is most often imagined as one of violent confrontation in the modern world. There should be an understanding between Buddhism and Islam to ensure peaceful coexistence among the adherents. Based on the arguments,this study aims to analyze peaceful coexistence through two different concepts, Brahmavihārās from Buddhism and Maqāṣidh al-Sharīʿa from Islam. Primarily it seeks to analyze these two concepts within their respective religions for a better comparison. It uses a library-based qualitative method. For this purpose, the research adopts the content analysis method, which focuses on the materials from journals, books, written reports, and other materials. The study highlights that even though Buddhism and Islam have different doctrinal foundations, the basic teachings promote peaceful coexistence from different points of view. This research concludes that both religions share similar concepts of peaceful coexistence which denote and declare human dignity as a right that should be paid attention. Both religions prioritize love and justice as the main standard in discussing peaceful coexistence. Hopefully, this conceptual study will be able to show that these two ideas are very significant and valuable when dealing with religious conflicts, to make a better inter-religious understanding among Buddhists and Muslims and to succeed in a process of reconciliation and for peaceful coexistence among diverse religious people.